Personal Branding Model of Conventional Kiai in Broadcasting Islamic Religion in Islamic Boarding Schools - Asep Iwan Setiawan; Siti Sumijaty; Dyah Rahmi Astuti (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2022)
This study aims to describe the process of establishing the personal branding of conventional kiai at Islamic boarding schools in Indonesia, starting from the stage of determining unique personal branding competencies, the stage of building connections and relationships, the stage of creating creativity to the controlling stage. The model used in this study is the personal branding circle-p model (competency, connectivity, creation, compliance, contribution). The paradigm used is a constructivist paradigm with an interpretive approach and descriptive method. Research data were collected through in-depth interviews and passive participatory observation. The study results show that the formation of personal branding is carried out through the stages of determining unique competencies, establishing relationships, creating creativity, and controlling that is carried out in a flowing manner seen from changes in attitudes and responses of students and other congregations from each meeting.